Stereological Evaluation of the Kidneys of Anencephalic and Normal Fetuses. (February 2013) - Kalaycioglu, Ahmet; Ucuncu, Yilmaz; Altunkaynak, Berrin Zuhal; Altunkaynak, Muhammed Eyüp; Gundogdu, Cemal; Keles, Osman Nuri; Unal, Bunyami; Kaplan, Suleyman
<x xml:space="preserve">Abstract</x> The aim of this study is to test the glomerular and other quantitative parameters of kidneys of anencephalic fetuses and comparing those to "normal" fetuses. In this study, 20 kidneys of human fetuses (5 boys and 5 girls of anencephalic fetus, and 5 boys and 5 girls of normal fetus), at gestational ages of 25–30 weeks, were examined. This study is based on two basic research methods: one is a conventional anatomical measurement at the macroscopical level; the other is a design-biased stereological method at the microscopical level. Physical dissector and Cavalieri principle were used to estimate the total and numerical density of glomerulus and the volume of kidney, respectively. The results of the two types of investigation were compared based on anencephalic/normal and boy/girl kidneys at both the macroscopical and microscopical levels. There was no significant difference found between the quantitative features of kidneys (volume of kidneys and mean number and/or height of glomerulus) belonging to anencephalic and normal fetuses. The results of this study suggest that anencephalic fetuses did not differ from normal fetuses in respect of kidneys.